Facile synthesis of rubrolide E - Kar, Anirban; N. P. Argade (Synthesis-Stuttgart, 2005)
A simple and efficient synthesis of rubrolide E (1e) has been demonstrated via Meerwein coupling reaction of para-anisyl-diazonium chloride with N-phenylmaleimide (2), regioselective reduction of para-anisylmaleic anhydride (4), Knoevenagel condensation of butyrolactone 5 with para-anisaldehyde and demethylation pathway.
Keywords: Knoevenagel condensation; Meerwein coupling; N-phenylmaleimide; regioselective reduction; rubrolide E; Total synthesis